Deep Siamese Metric Learning: A Highly Scalable Approach to Searching Unordered Sets of Trajectories - Löffler, Christoffer; Reeb, Luca; Dzibela, Daniel; Marzilger, Robert; Witt, Nicolas; Eskofier, Björn; Mutschler, Christopher (ACM Transactions on Intelligent Systems and Technology, 2022)
This work proposes metric learning for fast similarity-based scene retrieval of unstructured ensembles of trajectory data from large databases. We present a novel representation learning approach using Siamese Metric Learning that approximates a distance preserving low-dimensional representation and that learns to estimate reasonable solutions to the assignment problem. To this end, we employ a Temporal Convolutional Network architecture that we extend with a gating mechanism to enable learning from sparse data, leading to solutions to the assignment problem exhibiting varying degrees of sparsity.Our experimental results on professional soccer tracking data provides insights on learned features and embeddings, as well as on generalization, sensitivity, and network architectural considerations. Our low approximation errors for learned representations and the interactive performance with retrieval times several magnitudes smaller shows that we outperform previous state of the art.
CRIS-Team Scopus Importer:2022-03-04
Keywords: assignment problem; metric learning; Siamese neural networks